High adhesion fine line dry film and method of making same
Patent Information
- Application Number
- CN202610451329.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-08
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-04-08
AI Technical Summary
[0003]感光干膜产品主要由光固化树脂、光聚合单体、光引发剂及填料等物质组成,在精细线路制备中普遍存在附着力不足的问题,具体表现为与铜箔基材界面结合强度低,易在蚀刻、电镀等后续工艺中出现起翘、剥离、渗镀等缺陷,导致线路短路或断路,严重影响产品合格率
本发明公开了一种高附着力精细线路干膜,所述线路干膜由光固化树脂与可聚合单体、环氧丙烯酸酯、改性填料以及助剂等成分组成。本发明的环氧丙烯酸酯和改性填料均引入了大豆素二缩水甘油醚,一方面通过大豆素的结构改善了体系的力学性能、高低温稳定性,另一方面引入了大量环氧基,有效提高了膜层的粘附效果,提升了产品的附着力。同时,本发明的改性填料与基体树脂等组分的亲和性良好,在含量较高的前提下能均匀分散,且能通过环氧基与其他组分进行交联,并形成分子间作用力,由此提高了多种组分之间的结合效果,保证了干膜的精度和分辨率以及强度等综合性能。另外,为避免交联程度增加导致膜层韧性受到影响,本发明还采用烯丙基羟基聚醚作为活性单体,该物质不仅能发挥流平、分散的功能,还将柔性聚醚链段引入薄膜体系,搭配小分子增塑剂能进一步降低内应力,加强分子链的活动能力,从而保证了干膜的柔韧性。
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of dry film technology for printed circuit boards, and in particular to a high-adhesion fine printed circuit dry film and its preparation method. Background Technology
[0002] As the electronics and information industry rapidly develops towards high density, miniaturization, and high integration, the requirements for the precision of printed circuit boards (PCBs) are becoming increasingly stringent. Fine-line dry film, as a core material for achieving high-precision pattern transfer in PCB manufacturing, directly determines the yield and reliability of circuit production. Currently, mainstream fine-line processes demand increasingly higher resolution, while traditional dry films face multiple technical bottlenecks in addressing this trend.
[0003] Photosensitive dry film products are mainly composed of photocurable resins, photopolymerizable monomers, photoinitiators, and fillers. In the fabrication of fine circuits, insufficient adhesion is a common problem, specifically manifested as low interfacial strength with the copper foil substrate. This makes them prone to defects such as peeling, delamination, and plating defects during subsequent processes like etching and electroplating, leading to short circuits or open circuits and severely impacting product yield. Furthermore, increasing crosslinking density in pursuit of high resolution often results in decreased dry film toughness and increased brittleness, making it more susceptible to cracking under bending or thermal shock conditions, further exacerbating the risk of adhesion failure.
[0004] To improve adhesion, existing technologies often employ physical methods such as roughening the substrate surface or adding polar monomers. However, physical methods are limited by substrate characteristics and can easily damage circuitry, while chemical methods struggle to balance the conflict between adhesion and system flexibility. Some technologies introduce epoxy-modified resins to enhance interfacial bonding, but traditional epoxy systems suffer from excessive rigidity after curing, poor compatibility with acrylic systems, and a lack of targeted modification of filler surface properties, leading to uneven filler dispersion and affecting the developing accuracy of the dry film and the roughness of circuit edges. While existing methods also include filler modification techniques, the bonding effect with plasticizers and resins is not ideal, making it difficult to achieve comprehensive optimization of the overall performance of the dry film.
[0005] Furthermore, traditional dry films exhibit more pronounced adhesion problems when dealing with complex substrates (such as flexible substrates and thick copper substrates), and are prone to moisture absorption and delamination in high-temperature and high-humidity environments, failing to meet the reliability requirements of high-end applications such as automotive electronics and 5G communications. Therefore, how to solve the technical challenges of insufficient adhesion and the difficulty in balancing flexibility and resolution in traditional dry films has become a key issue that urgently needs to be addressed in this field.
[0006] Therefore, it is necessary to provide a new technical solution to overcome the defects existing in the prior art. Summary of the Invention
[0007] Based on this, the present invention provides a high-adhesion fine circuit dry film and its preparation method. The present invention uses epoxy acrylate, modified filler and other substances combined with organic resin and other components to introduce a variety of active functional groups. While improving the adhesion of the dry film, it effectively improves the binding effect between components, thereby exerting a synergistic effect, enhancing the overall performance of the product, and meeting the current industry requirements for the performance of fine circuit dry films.
[0008] One object of the present invention is to provide a high-adhesion fine circuit dry film, the high-adhesion fine circuit dry film comprising the following components in parts by weight: 20-40 parts of UV-curable resin 5-12 parts of polymerizable monomer 1-5 parts epoxy acrylate 5-15 parts of modified filler Photoinitiator 0.1-5 parts 0.1-5 parts of additives Solvent 10-30 parts; in, The modified filler is obtained by reacting an amino-modified filler with soybean diglycidyl ether.
[0009] Furthermore, the epoxy acrylate is obtained by reacting soybean diglycidyl ether with acrylic acid.
[0010] Furthermore, the polymerizable monomer includes allyl polyether.
[0011] Furthermore, the filler is selected from one or more of boron nitride, silicon carbide, silicon dioxide, aluminum hydroxide, aluminum oxide, zinc oxide, and talc.
[0012] Furthermore, the additive is selected from one or more of plasticizers, crosslinking agents, dispersants, pigments, leveling agents, curing agents, and antioxidants.
[0013] Specifically, the structural formula of the soybean diglycidyl ether is: .
[0014] Another object of the present invention is to provide a method for preparing the above-mentioned high-adhesion fine circuit dry film, wherein the method for preparing the high-adhesion fine circuit dry film includes the following steps: S1. Soybean diglycidyl ether, acrylic acid, catalyst and polymerization inhibitor are mixed and heated to react, and then epoxy acrylate is obtained. S2. Mix the amino-modified filler, soybean diglycidyl ether and catalyst, and heat to react to obtain the modified filler. S3. Mix the epoxy acrylate, modified filler and other components, coat it onto the substrate, dry it and cover it with a protective film to obtain the high adhesion fine circuit dry film.
[0015] Further, in step S1, the mass ratio of soy diglycidyl ether to acrylic acid is 1:(0.1-0.5).
[0016] Furthermore, in step S1, the heating reaction is carried out at a temperature of 100-120°C for 5-20 hours.
[0017] Further, in step S2, the mass ratio of the amino-modified filler to soybean diglycidyl ether is 1:(0.1-2).
[0018] Furthermore, in step S2, the heating reaction is carried out at a temperature of 80-100°C for 5-10 hours.
[0019] The present invention has the following beneficial effects: This invention discloses a high-adhesion fine circuit dry film, which is composed of a photocurable resin, polymerizable monomers, epoxy acrylate, modified fillers, and additives. Both the epoxy acrylate and the modified filler of this invention incorporate daidzein diglycidyl ether. On the one hand, the structure of daidzein improves the mechanical properties and high / low temperature stability of the system; on the other hand, the introduction of a large number of epoxy groups effectively improves the adhesion of the film layer and enhances the product's adhesion. Simultaneously, the modified filler of this invention exhibits good affinity with the matrix resin and other components, achieving uniform dispersion even at high concentrations. Furthermore, it can crosslink with other components through epoxy groups, forming intermolecular forces, thereby improving the bonding effect between various components and ensuring the overall performance of the dry film, including precision, resolution, and strength. In addition, to avoid increased crosslinking affecting the film's toughness, this invention also uses allyl hydroxyl polyether as an active monomer. This substance not only performs leveling and dispersing functions but also introduces flexible polyether segments into the film system. Combined with small-molecule plasticizers, it further reduces internal stress and enhances the mobility of molecular chains, thus ensuring the flexibility of the dry film. Detailed Implementation
[0020] To more clearly illustrate the technical solution of the present invention, the following embodiments are provided. Unless otherwise stated, the raw materials, reactions, and post-processing methods appearing in the embodiments are all commercially available raw materials and technical methods well known to those skilled in the art.
[0021] The terms "preferred," "more preferably," and "more suitable" used in this invention refer to embodiments of the invention that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this invention.
[0022] It should be understood that, except in any operational instance or otherwise indicated, all figures representing the amounts of ingredients used, for example, in the specification and claims, should be understood to be modified in all cases by the term "about". Therefore, unless otherwise stated, the numerical parameters set forth in the following specification and appended claims are approximations varying with the desired performance to be obtained according to the invention.
[0023] In the embodiments of the present invention, the photocurable resins are Sartoma SB520A20 and Sartoma CN1073NS in a mass ratio of 3:1.
[0024] In the embodiments of the present invention, the allyl polyether is APEG400; and the bisphenol A dimethacrylate ester is Changxing EM3260.
[0025] In this embodiment of the invention, the photoinitiator is BCIM.
[0026] The plasticizer used in this embodiment of the invention is p-toluenesulfonamide.
[0027] The solvent used in the embodiments of the present invention is a divalent ester.
[0028] Example 1 A high-adhesion fine circuit dry film, wherein the high-adhesion fine circuit dry film comprises the following components in parts by weight: 20 parts of UV-curable resin 1 part allyl polyether 2 parts hydroxyethyl acrylate 2 parts of bisphenol A dimethacrylate oxyacetate 2 parts epoxy acrylate 5 parts of modified filler 1.5 parts photoinitiator 0.5 parts plasticizer 10 parts solvent; The method for preparing the high-adhesion fine circuit dry film includes the following steps: S1. Using diethylene glycol ethyl ether acetate as solvent, soybean diglycidyl ether, acrylic acid, triphenylphosphine and hydroquinone in a mass ratio of 100:25:2:1 were mixed, heated to 110℃ and stirred for 12 h. After removing the solvent, epoxy acrylate was obtained. S2. Using 90 wt% ethanol-water solution as solvent, boron nitride and KH-550 were mixed in a mass ratio of 1:0.5 and heated under reflux for 12 h. After filtration, washing and drying, amino-modified filler was obtained. Using N-methylpyrrolidone as a solvent, the amino-modified filler, soybean diglycidyl ether, and 4-dimethylaminopyridine were mixed (the mass ratio of amino-modified filler, soybean diglycidyl ether, and DMAP was 1:0.6:0.01), reacted at 95°C for 6 h, filtered, dried, and ground to a particle size ≤4 μm to obtain the modified filler. S3. Mix the epoxy acrylate, modified filler and other components evenly according to the above mass proportions, then coat it onto a PET film substrate, dry it at 80°C, and cover it with a PE protective film to form a sandwich structure, thereby obtaining the high adhesion fine circuit dry film (intermediate layer thickness is 20 μm).
[0029] Example 2 A high-adhesion fine circuit dry film, wherein the high-adhesion fine circuit dry film comprises the following components in parts by weight: 30 parts of UV-curable resin 1.4 parts allyl polyether 3.2 parts hydroxyethyl acrylate 3 parts of bisphenol A dimethacrylate oxyacetate 3.2 parts epoxy acrylate 7 parts of modified filler 2.2 parts of photoinitiator 0.9 parts plasticizer 15 parts solvent; The method for preparing the high-adhesion fine circuit dry film includes the following steps: S1. Using diethylene glycol ethyl ether acetate as solvent, soybean diglycidyl ether, acrylic acid, triphenylphosphine and hydroquinone in a mass ratio of 100:25:2:1 were mixed, heated to 110℃ and stirred for 12 h. After removing the solvent, epoxy acrylate was obtained. S2. Using 90 wt% ethanol-water solution as solvent, boron nitride and KH-550 were mixed in a mass ratio of 1:0.5 and heated under reflux for 12 h. After filtration, washing and drying, amino-modified filler was obtained. Using N-methylpyrrolidone as a solvent, the amino-modified filler, soybean diglycidyl ether, and 4-dimethylaminopyridine were mixed (the mass ratio of amino-modified filler, soybean diglycidyl ether, and DMAP was 1:0.6:0.01), reacted at 95°C for 6 h, filtered, dried, and ground to a particle size ≤4 μm to obtain the modified filler. S3. Mix the epoxy acrylate, modified filler and other components evenly according to the above mass proportions, then coat it onto a PET film substrate, dry it at 80°C, and cover it with a PE protective film to form a sandwich structure, thereby obtaining the high adhesion fine circuit dry film (intermediate layer thickness is 20 μm).
[0030] Example 3 A high-adhesion fine circuit dry film, wherein the high-adhesion fine circuit dry film comprises the following components in parts by weight: 40 parts of UV-curable resin 1.9 parts allyl polyether 4 parts of hydroxyethyl acrylate 4.5 parts of bisphenol A dimethacrylate oxyacetate 4 parts epoxy acrylate 11 parts of modified filler 3 parts of photoinitiator 1.2 parts plasticizer 22 parts solvent; The method for preparing the high-adhesion fine circuit dry film includes the following steps: S1. Using diethylene glycol ethyl ether acetate as solvent, soybean diglycidyl ether, acrylic acid, triphenylphosphine and hydroquinone in a mass ratio of 100:25:2:1 were mixed, heated to 110℃ and stirred for 12 h. After removing the solvent, epoxy acrylate was obtained. S2. Using 90 wt% ethanol-water solution as solvent, boron nitride and KH-550 were mixed in a mass ratio of 1:0.5 and heated under reflux for 12 h. After filtration, washing and drying, amino-modified filler was obtained. Using N-methylpyrrolidone as a solvent, the amino-modified filler, soybean diglycidyl ether, and 4-dimethylaminopyridine were mixed (the mass ratio of amino-modified filler, soybean diglycidyl ether, and DMAP was 1:0.6:0.01), reacted at 95°C for 6 h, filtered, dried, and ground to a particle size ≤4 μm to obtain the modified filler. S3. Mix the epoxy acrylate, modified filler and other components evenly according to the above mass proportions, then coat it onto a PET film substrate, dry it at 80°C, and cover it with a PE protective film to form a sandwich structure, thereby obtaining the high adhesion fine circuit dry film (intermediate layer thickness is 20 μm).
[0031] Comparative Example 1 The difference between this comparative example and Example 1 is that step S1 is deleted, and epoxy acrylate is replaced with an equal mass of bisphenol A dimethacrylate. Other components and preparation methods are the same as in Example 1.
[0032] Comparative Example 2 The difference between this comparative example and Example 1 is that step S2 is modified as follows: Using 90 wt% ethanol-water solution as solvent, boron nitride and KH-560 were mixed at a mass ratio of 1:0.5 and heated under reflux for 12 h. After filtration, washing, drying, and grinding to a particle size ≤4 μm, boron nitride epoxide was obtained. Other components and preparation methods were the same as in Example 1.
[0033] Test case The samples prepared in the examples and comparative examples were subjected to performance tests.
[0034] Test method: The circuit dry films prepared in the examples and comparative examples were bonded to the surface of the copper-clad laminate at a roller temperature of 110°C and a pressure of 400 mJ / cm. 2 Exposure, followed by development with a 1 wt% sodium carbonate aqueous solution (temperature 30°C, spray pressure 1.5 kg / cm). 2 Then wash and dry.
[0035] Resolution: Using a chrome glass mask with a wiring pattern of n:n (n is 4-25 μm) with exposed and unexposed portions, exposure is performed. After complete development, the minimum mask width that forms a complete cured resist line is observed under a microscope and taken as the resolution value.
[0036] Adhesion: Use a needle tip to draw an "X" shape on the film, then stick cellophane tape on the marks and pull it. The evaluation criteria are as follows: Good: Not torn off; Medium: Tear off a small amount; Poor: A large amount was torn off.
[0037] Flexibility: With the dry film of the circuit as the inside, bend it 180° around an 8 mm diameter cylindrical shaft and evaluate it according to the following criteria: Pass: No cracks on the film; Unacceptable: The film has cracks.
[0038] Acid / alkali resistance: At 20°C, the sample is immersed in a 10 wt% sulfuric acid solution or a 10 wt% sodium hydroxide solution for 30 minutes. After immersion, the sample is removed and the coating condition and adhesion are evaluated. The evaluation criteria are as follows: Pass: No changes or slight changes were found; Unacceptable: The coating shows swelling or swelling and peeling.
[0039] Impact resistance: Copper-clad laminate samples with dry film coating were subjected to a thermal shock test using a thermal shock testing machine, with 1000 cycles of -55℃ / 30 min to 150℃ / 30 min as one cycle. After the test, the coating condition and adhesion were evaluated based on the following criteria: Acceptable: Crack initiation rate < 50%; Unacceptable: Crack infestation rate ≥ 50%.
[0040] The test results are shown in Table 1.
[0041] Table 1 Performance Test Results As shown in Table 1, the high-adhesion fine circuit dry film of the present invention exhibits excellent comprehensive performance. It not only possesses high resolution but also demonstrates good adhesion, flexibility, acid and alkali resistance, and stability, meeting the performance requirements of circuit dry films under different environments. In contrast, Comparative Example 1, by replacing epoxy acrylate, reduced the epoxy group content, resulting in decreased adhesion. Due to the increased content of multifunctional monomers, the crosslinking density increased, leading to a decrease in toughness. Comparative Example 2, by replacing the modified filler and not introducing the soybean glycoside structure, significantly impacted the overall performance of the dry film, with several properties falling short of expectations.
[0042] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0043] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A high-adhesion fine circuit dry film, characterized in that, The high-adhesion fine circuit dry film comprises the following components in parts by weight: 20-40 parts of UV-curable resin 5-12 parts of polymerizable monomer 1-5 parts epoxy acrylate 5-15 parts of modified filler Photoinitiator 0.1-5 parts 0.1-5 parts of additives Solvent 10-30 parts; in, The modified filler is obtained by reacting an amino-modified filler with soybean diglycidyl ether; The epoxy acrylate is obtained by reacting soybean diglycidyl ether and acrylic acid. The filler is selected from one or more of boron nitride, silicon carbide, silicon dioxide, aluminum hydroxide, aluminum oxide, zinc oxide, and talc.
2. The high-adhesion fine circuit dry film according to claim 1, characterized in that, The polymerizable monomers include allyl polyethers.
3. The high-adhesion fine circuit dry film according to claim 1, characterized in that, The additives are selected from one or more of plasticizers, crosslinking agents, dispersants, pigments, leveling agents, curing agents, and antioxidants.
4. The method for preparing the high-adhesion fine circuit dry film according to any one of claims 1-3, characterized in that, The method for preparing the high-adhesion fine circuit dry film includes the following steps: S1. Soybean diglycidyl ether, acrylic acid, catalyst and polymerization inhibitor are mixed and heated to react, and then epoxy acrylate is obtained. S2. Mix the amino-modified filler, soybean diglycidyl ether and catalyst, and heat to react to obtain the modified filler. S3. Mix the epoxy acrylate, modified filler and other components, coat it onto the substrate, dry it and cover it with a protective film to obtain the high adhesion fine circuit dry film.
5. The method for preparing a high-adhesion fine circuit dry film according to claim 4, characterized in that, In step S1, the mass ratio of soybean diglycidyl ether to acrylic acid is 1:(0.1-0.5).
6. The method for preparing a high-adhesion fine circuit dry film according to claim 4, characterized in that, In step S1, the heating reaction is carried out at a temperature of 100-120°C for 5-20 hours.
7. The method for preparing a high-adhesion fine circuit dry film according to claim 4, characterized in that, In step S2, the mass ratio of the amino-modified filler to soybean diglycidyl ether is 1:(0.1-2).
8. The method for preparing a high-adhesion fine circuit dry film according to claim 4, characterized in that, In step S2, the heating reaction is carried out at a temperature of 80-100℃ for 5-10 hours.
Citation Information
Patent Citations
Biomass-based easily degradable synthetic resin and preparation method thereof
CN118240221A
High-performance photocuring solder resist ink based on biomass daidzein and preparation method of high-performance photocuring solder resist ink
CN119371390A